Answer:
[tex]1.\ y = 2x - 1[/tex]
[tex]2.\ y = -4x + 5[/tex]
Step-by-step explanation:
Solving (1): The line equation in y intercept form;
Given
[tex]m = 2[/tex]
[tex](x_1,y_1) = (4,7)[/tex]
This is calculated using the following formula
[tex]y - y_1 = m(x - x_1)[/tex]
Substitute values for m, x1 and y1
[tex]y - 7 = 2(x - 4)[/tex]
Open Bracket
[tex]y - 7 = 2x - 8[/tex]
Make y the subject
[tex]y = 2x - 8 + 7[/tex]
[tex]y = 2x - 1[/tex]
Solving (2): The line equation in y intercept form;
Given
[tex]m = -4[/tex]
[tex](x_1,y_1) = (-1,9)[/tex]
This is calculated using the following formula
[tex]y - y_1 = m(x - x_1)[/tex]
Substitute values for m, x1 and y1
[tex]y - 9 = -4(x - (-1))[/tex]
[tex]y - 9 = -4(x + 1)[/tex]
Open Bracket
[tex]y - 9 = -4x - 4[/tex]
Make y the subject
[tex]y = -4x - 4 + 9[/tex]
[tex]y = -4x + 5[/tex]